Spline Model in The Case of Cervical Cancer Patient Resilience - Hidayat, Rahmat; Ilyas, Muhammad; Yuliani, Yuliani (Trends in Sciences, 2023)
Cervical cancer ranks highest in developing countries, and ranks 10th in developed countries as a cause of death for women. In Indonesia, cervical cancer ranks second out of the 10 most common cancers based on Anatomical Pathology data in 2010 with an incidence rate of 20 %. The number of new women with cervical cancer ranges from 90 - 100 cases per 100,000 population and every year there are 40 thousand cases of cervical cancer. Cervical cancer is a gynecological disease that has a high level of malignancy and is caused by the Human Papilloma Virus (HPV). One method that can be used in the analysis of human survival is survival analysis using the Cox proportional hazard model. This research will use the development of the Cox model using the Spline function as its basis. Based on the results obtained, the developed model can model the data well and give a low MSE. Based on the developed model, it is found that the variables that influence the survival rate of cervical cancer patients are age, stage, type of PRC transfusion treatment and comorbidities. HIGHLIGHTS Due to in silico study such as molecular docking, molecular dynamic simulation is an important computational method for drug design. It can be used to predict the binding orientation of small molecule drug candidates to their protein targets. In addition, docking is also can be applied to predict small molecule affinity and activity. Thus, molecular docking has an important role in drug discovery and rational design The ligand interaction with the receptor was more stable due to the decreased binding free energy value The lowest binding free energy and lowest RMSD value of this molecule, which may presumably cause compound 3 to has better binding affinity compare to other compounds GRAPHICAL ABSTRACT